Diction in Poetry Anthologies Mengapa Luka Tidak Memaafkan Pisau M Aan Mansyur's Work and Its Use as Poetry Teaching Material in High School - Kusnasari, Zanida Zulfana; Rakhmawati, Ani; Mulyono, Slamet (Jurnal Ilmiah Mandala Education (JIME), 2024)
Learning poetry at the high school level in Indonesia is generally expected to provide a deeper understanding of literature and enrich students' language skills, but in reality, there is a lack of understanding of the building blocks and values of poetry, as well as limited teaching materials that are effective in facilitating understanding and appreciation of works. poetry. This analysis will be carried out with the aim of finding the use of diction in the poetry anthology Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur and analyzing its use as poetry teaching material in high school. This research uses a qualitative approach. The type of research used in this research is content analysis. By using content analysis, researchers can dig deeper into the use of diction in the poetry anthology Mengapa Luka Tidak Memaafkan Pisau by M. Aan Mansyur and its use as poetry teaching material in high school. Based on the research results, it was found that the dominant diction used in this anthology was connotation with a total of 107 words or a percentage of 69.5%. The results showed that the diction